Fundamentals of Browlift - Viterbo, Fausto [UNESP]; Neto, Balduíno [UNESP]; Magnani, Lucas [UNESP] (Springer Nature, 2024)
Brow lift surgery has always been a challenge for plastic surgeons. Therefore, many techniques were developed and disseminated, requiring a broad knowledge of the training specialist. On the one hand, the open techniques stood out for their ease of execution, while the video techniques required specific material and some extra training. As there is no consensus, it is fundamental that we know the advantages and disadvantages of each one of them, to offer the best for our patients, individualizing the treatment. At the end of this chapter, the surgeon will learn or at least remember fundamental concepts of different techniques applied in various parts of the world.